Growth and characterization of a new organic nonlinear optical crystal: 1-(3-Nitrophenyl)-5-phenylpenta-2, 4-dien-1-one. (August 2015) - Patil, P.S.; Kumar, P. Ajay; Venugopal Rao, S.; Bhagavannarayana, G.
Abstract: Organic nonlinear optical single crystal of 1-(3-Nitrophenyl)-5-phenylpenta-2, 4-dien-1-one (Ci3NC) with dimensions 25×15×10 mm 3 was successfully grown for the first time by the slow evaporation solution growth technique (SEST). The structural perfection of the grown crystals has been analyzed by high-resolution X-ray diffraction (HRXRD) rocking curve measurements, and it was found that the crystalline perfection is reasonably good having very low angle (tilt angle ≤1′) internal structural grain boundary. Thermo-gravimetric analysis (TGA) and differential thermal analysis (DTA) were used to study its thermal properties. Powder test with Nd:YAG laser radiation shows second harmonic generation which is about 7 times that of urea. The optical transmittance window and the lower cutoff wavelength of the Ci3NC have been identified by UV–vis–NIR studies. Third-order nonlinear optical (NLO) response of Ci3NC has been examined using Z-scan technique with femtosecond (fs), MHz pulses at wavelengths of 870 nm and 900 nm. Various NLO coefficients such as two-photon absorption (2PA) coefficient ( β ), three photon absorption (3PA) coefficient ( γ ), and nonlinear refractive index ( η 2 ) were evaluated. Highlights: Good quality crystals of Ci3NC were grown by slow evaporation solution growth method. Powder SHG efficiency is 7 times that of urea. HRXRD results confirm that the crystalline perfection is reasonably good. Observed 3PA with 80 MHz excitation and 2PA with lower repetition rate (1 kHz and 500 Hz data).